Vegetation Science Applications for Rangeland Analysis and Management 1988
DOI: 10.1007/978-94-009-3085-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Rangeland vegetation productivity and biomass

Abstract: Herbage weight or biomass is an important characteristic for range vegetation since it supports directly or indirectly all consumer groups. Plant biomass is also important as a measure of dominance in plant communities. Many methods have been devised to estimate plant biomass, but all have some limitations. Estimation techniques, either by plot or plant, often involve a double sampling procedure to improve on the estimates. Direct harvesting is a destructive sampling procedure which is often used when biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…for each pasture type based on Tothill and Gilles (1992) (Figure S18 and S19, Table S7). The pasture consumption per adult equivalent was set at 9 kg per day (± 1 kg per day) based on a range of studies (Queensland Government Department of Agriculture Forestry and Fisheries (DAFF) 2013, Scanlan et al 1994, Pieper 1988, Holechek 1988, Walsh and Cowley 2011, Bernado 1989, and multiplied by 365 to give an annual value. We constrained the model to the broad area currently grazed by livestock to avoid unsuitable vegetation types, soils, or topographies, and ensure appropriate land tenure (primarily pastoral leasehold).…”
Section: Simulations Of Safe Stocking Ratesmentioning
confidence: 99%
“…for each pasture type based on Tothill and Gilles (1992) (Figure S18 and S19, Table S7). The pasture consumption per adult equivalent was set at 9 kg per day (± 1 kg per day) based on a range of studies (Queensland Government Department of Agriculture Forestry and Fisheries (DAFF) 2013, Scanlan et al 1994, Pieper 1988, Holechek 1988, Walsh and Cowley 2011, Bernado 1989, and multiplied by 365 to give an annual value. We constrained the model to the broad area currently grazed by livestock to avoid unsuitable vegetation types, soils, or topographies, and ensure appropriate land tenure (primarily pastoral leasehold).…”
Section: Simulations Of Safe Stocking Ratesmentioning
confidence: 99%
“…For each quadrat, a small sample (100 g) was collected and dried to a constant weight to determine percent moisture. Percent moisture for the clipped vegetation was applied to the mass recorded for the quadrat to estimate the dry forage mass in kg/ha [47].…”
Section: Field Data Collectionmentioning
confidence: 99%
“…The distance was maintained at 550 m and 300 m, between transects and plots, respectively. In each plot, parameters such as herbaceous biomass productivity, trees stocking parameters (standing density, diameter at breast height and tree height), and soil samples were enumerated and recorded as per (Behera et al, 2017;Pieper, 1988;Rubanza et al, 2006) as shown below:…”
Section: Study Design and Forest Inventorymentioning
confidence: 99%